1999
DOI: 10.1063/1.125283
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of electron emission site on boron-doped polycrystalline diamond thin films using an ultra-high-vacuum scanning tunneling microscope

Abstract: Articles you may be interested inScanning tunneling microscopy observations of hafnium carbide thin films as a field emission material J. Vac. Sci. Technol. B 23, 741 (2005); 10.1116/1.1849192 Current image tunneling spectroscopy of boron-doped nanodiamonds J. Appl. Phys. 97, 044312 (2005); 10.1063/1.1834722 Development of an in situ ultra-high-vacuum scanning tunneling microscope in the beamline of the 15 MV tandem accelerator for studies of surface modification by a swift heavy ion beam Rev. Sci. Instrum. 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…3 Using thin film diamond will overcome these limits as diamond films are known to show exceptional hardness, 4 wear-resistance, 5 chemical stability, and high thermal conductivity 6 in addition to optical transparency from deep UV to far infrared. [7][8][9][10] In this paper we show that diamond thin films are also suitable for tuneable microlens applications which are planned to be implemented in arthroscopic microsurgery devices where biocompatibility, chemical stability, and optical properties are of high importance.…”
mentioning
confidence: 93%
“…3 Using thin film diamond will overcome these limits as diamond films are known to show exceptional hardness, 4 wear-resistance, 5 chemical stability, and high thermal conductivity 6 in addition to optical transparency from deep UV to far infrared. [7][8][9][10] In this paper we show that diamond thin films are also suitable for tuneable microlens applications which are planned to be implemented in arthroscopic microsurgery devices where biocompatibility, chemical stability, and optical properties are of high importance.…”
mentioning
confidence: 93%
“…Diamond has been considered as a prospective material for field emission because of its low or negative electron affinities, as well as its thermal, chemical and mechanical stabilities [1][2][3][4]. Experimental results have shown that field emission from a thin sheet of molybdenum coated with diamond is greatly enhanced, as compared with that of uncoated diamond [5,6].…”
Section: Introductionmentioning
confidence: 93%
“…For electrical applications, we required the fabrication of lowresistivity n-type and p-type material by doping diamond with donor and acceptor impurities, respectively. However, n-type conduction of diamond is basically more challenging than p-type, which has already been achieved by B-doping [1][2][3][4]. In recent years, the researchers have focused on nitrogen, phosphorus and sulfur doping primarily.…”
Section: Introductionmentioning
confidence: 99%